2012
DOI: 10.2320/matertrans.m2012282
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Temperature on the Structure and Cohesive/Adhesive Strength of Fe–Co–Si–B–Nb Metallic Glass Coating Films Produced by Thermal Spraying

Abstract: The influence of the substrate temperature on the structure, pore distribution and cohesive/adhesive strength of FeCo-based metallic glass coating films has been examined. The metallic glass coating films have been produced by a thermal spraying technique using our developed cylindrical nozzle on SS400 substrates. The splat morphology of the sprayed particles changed from an irregular splash to a disk shape at a transition temperature of about 300°C. When the substrate temperature increased to the transition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Additionally, little oxidization is also expected to be obtained. 24,25) Because the elongation of the coated bolt was greater than that of the naked bolt, it was confirmed that less hydrogen embrittlement occurred in the coated bolt than in the naked bolt as shown in Fig. 7.…”
Section: Prevention Of Hydrogen Embrittlement By Alumi-mentioning
confidence: 49%
“…Additionally, little oxidization is also expected to be obtained. 24,25) Because the elongation of the coated bolt was greater than that of the naked bolt, it was confirmed that less hydrogen embrittlement occurred in the coated bolt than in the naked bolt as shown in Fig. 7.…”
Section: Prevention Of Hydrogen Embrittlement By Alumi-mentioning
confidence: 49%
“…The adhesion strength slightly improved because of the increase in temperature, which affected the sprayed particles along the interface. Komaki et al [31,32] stated that the structure of particles and pores along the coating-substrate interface affect the adhesion strength. An increase in temperature improved the wettability of particles along the interface, thus improving the bonding of splat particles.…”
Section: Tensile Bonding Strengthmentioning
confidence: 99%
“…Sonuç olarak altlık malzemesi olarak kullanılan aluminyum ve çelik plakaların yüzey sertlikleri, yüzeylerine kaplanan amorf tabaka sayesinde yaklaşık 1000 Hv sertlik değerine yükselmiştir. Ölçülen sertlik değeri Komaki ve ark.nın termal spreyleme yöntemi ile ürettikleri CoFe-esaslı kaplama ile uyumludur [Komaki M. Et al. , 2012].…”
Section: Tartışma Ve Sonuçunclassified